The Wiley Handbook of Violence and Aggression 2017
DOI: 10.1002/9781119057574.whbva050
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Conceptualization, Measurement, and Analysis of Family Violence

Abstract: The traditional—and still prevalent—model of family violence primarily focuses on individuals as either perpetrators or victims. However, research demonstrates that violence within couples does not occur within a vacuum, is dynamic, and typically involves behaviors from both partners. In an attempt to incorporate a dyadic perspective to family violence, this chapter demonstrates why a dyadic perspective is important, outlines obstacles to obtaining dyadic data and methods for overcoming those obstacles, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To date, most empir i cal exam i na tions of the cor re lates of atti tudes toward IPV have used indi vid u als as the unit of anal y sis (for an excep tion, see Alio et al 2011) and have often focused on women (Cools and Kotsadam 2017;Pierotti 2013;Swindle 2018;Uthman et al 2010;Waltermaurer 2012). Yet IPV is inher ently a rela tional event that is shaped by cou ple-level dynam ics and indi vid ual-level char ac ter is tics (Conroy 2014;Ghuman et al 2006;Rodriguez and Straus 2017). Husbands and wives enter mar riage with their own lived expe ri ences and per spec tives, which inter act and are reshaped over time.…”
Section: Advance Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most empir i cal exam i na tions of the cor re lates of atti tudes toward IPV have used indi vid u als as the unit of anal y sis (for an excep tion, see Alio et al 2011) and have often focused on women (Cools and Kotsadam 2017;Pierotti 2013;Swindle 2018;Uthman et al 2010;Waltermaurer 2012). Yet IPV is inher ently a rela tional event that is shaped by cou ple-level dynam ics and indi vid ual-level char ac ter is tics (Conroy 2014;Ghuman et al 2006;Rodriguez and Straus 2017). Husbands and wives enter mar riage with their own lived expe ri ences and per spec tives, which inter act and are reshaped over time.…”
Section: Advance Publicationmentioning
confidence: 99%
“…Likewise, Swindle (2018) found that in Malawi, tele vi sion use is asso ci ated with higher accep tance of IPV among men, whereas tele vi sion use is asso ci ated with higher rejec tion of IPV among women. Very few studies have taken a dyadic perspective, examining the attitudes of male and female partners in conjunction (Conroy 2014;Rodriguez and Straus 2017).…”
Section: Temporal Cross-national and Gendered Variation In Attitudes Toward Ipvmentioning
confidence: 99%